From Xerox to Zoom: Brazilian universities during the coronavirus pandemic - Pait, Heloisa [UNESP] (University of Illinois Libraries, 2022)
Transmission of knowledge in Brazilian universities has been largely shaped by a Xerox culture of rapid reproduction of text, one that sits suspended between the print book and the Internet. The 2020 coronavirus pandemic disrupted the use of established means of communication in Brazilian undergraduate classrooms and forced higher education institutions to confront their concepts of education. Many Brazilian public universities stopped classes altogether and only resumed them online by mid-2020 or even later in the year, after much deliberation. This research examines how university officials responded to the new demand to implement remote teaching in their institutional and communicative contexts. Analyzing the very rich public and official statements produced by a set of prestigious Brazilian universities, this research reveals the ways in which the quarantine both challenged and mobilized the deepest values of the country’s higher education institutions. The goal of this research is to understand how a rigid communication culture, in which the values and histories of the institutions are crystalized, made adaptation to new teaching conditions very difficult. It presents a fascinating case where knowledge, media and institutional culture intersect in a moment of crisis.